(untitled) (Journal on studies and research of academic knowledge, 2016)
Samples of rice leaves (Oryza sativa L.) collected from 2014/2015 season were collected in the Itapúa, Misiones and Caazapá Departments with the aim of quantifying the main pathogens causing foliar rice diseases in Paraguay. Laboratory work included macroscopic and microscopic observations of symptoms and signs for quantification; exposure of materials in wet chambers; isolation in PDA culture media and purification with the hyphal tip method. The five pathogens with the highest incidence were Bipolaris oryzae (45,0%) , Alternaria padwickii (45,8%), Microdochium oryzae (15,0%), Cercospora spp (40,3%) and Pyricularia oryzae (9,5%).